2012
DOI: 10.1111/j.1399-3089.2012.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

The free radical scavenger S‐PBN significantly prolongs DSG‐mediated graft survival in experimental xenotransplantation

Abstract: The combination of S-PBN and DSG treatment increases xenograft survival. The main effect of S-PBN appears to be in direct connection with the transplantation. Because of its low toxicity, S-PBN could become useful in combination with other immunosuppressants to reduce cell-mediated xenograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…2 AHXR occurs within 3 days after transplantation in the mouse-to-rat and hamster-to-rat heart transplantation models, characterized by binding of different immunoglobulins (Ig) to the vascular endothelium, vasculitis, thrombosis, tissue destruction, and edema. 3 Turnquist et al 4 observed a potent ability of interleukin (IL)-33 to increase suppressive CD4 + Foxp3 + regulatory T cells (Tregs). Overall, fewer infiltrated T cells, but increased numbers of Tregs, were seen in the heart grafts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 AHXR occurs within 3 days after transplantation in the mouse-to-rat and hamster-to-rat heart transplantation models, characterized by binding of different immunoglobulins (Ig) to the vascular endothelium, vasculitis, thrombosis, tissue destruction, and edema. 3 Turnquist et al 4 observed a potent ability of interleukin (IL)-33 to increase suppressive CD4 + Foxp3 + regulatory T cells (Tregs). Overall, fewer infiltrated T cells, but increased numbers of Tregs, were seen in the heart grafts.…”
mentioning
confidence: 99%
“…To confirm the hypothesis, we used the concordant mouse-to-rat transplantation model, where the donor heart is heterotopically transplanted to the neck vessels of the recipient. 3 The combined use of IL-33 and Lef thus allowed us to study the impact of IL-33 on AVR. 13 Graft survival was determined in separate animals, and the activation and infiltration of immune cells were studied separately by flow cytometry.…”
mentioning
confidence: 99%
“…In experimental traumatic brain injury, S-PBN treatment reduced T-cell infiltration and adhesion-molecule expression on the endothelium. Biglarnia et al [10] hypothesized that S-PBN could also reduce infiltration of T cells during cell-mediated xenograft rejection and increase graft survival. To test this, a concordant mouse-to-rat heart transplantation model was used where recipients received no treatment or 15-deoxyspergualin (DSG) and S-PBN, alone or in combination.…”
Section: Small Animal Modelsmentioning
confidence: 99%